MASYARAKAT INDONESIA DALAM SERIBU WAjAH KAPITALISME - Luthfi, Asma (Forum Ilmu Sosial, 2009)
Basically, the existing capitalist system in Indonesia today is the economic system that has been practiced for a long time. Throughout its history, there are several forms of the capitalist system that has been practiced in Indonesia. The frst is the colonial capitalist system which lasted from the Dutch colonial period until Indonesia’s independence. The second is the bureaucratic capitalism that took place during the New Order period. The third is the global capitalist system that emerges when neo-liberalism policies are applied to the Third-World countries, including Indonesia. Such capitalist systems in their developments give either some implications or impacts to the social life of the people in Indonesia.Keywords: Indonesia people’s, capitalist system